Slums : how informal real estate markets work - Chattaraj, Shahana; Wachter, Susan M.; Birch, Eugenie Ladner (City in the twenty-first century book series., 2016)
Slums: How Informal Real Estate Markets Work shows that unauthorized settlements in rapidly growing cities are not divorced from market forces; rather, they must be understood as complex environments where state policies and market actors play a role.